Trajectory tracking of quaternion based quadrotor using model predictive control - Islam, Maidul; Okasha, Mohamed Elsayed Aly Abd Elaziz; Idres, Moumen; Mansor, Hasmah (Science Publishing Corporation Inc, 2018)
The aim of this paper is to introduce the trajectory tracking with a quaternion based quadrotor operation using model predictive con-trol (MPC). Since the efficacy of MPC on a system under noise and disturbance has been distinguished, it is a fair and successful attempt to apply MPC on the quaternion based quadrotor, which is a quite well-known system with uncertainties during operation. Quaternion approaches singularity-free orientation that is advantageous to design any trajectory for quadrotor wherein roll or pitch angle reaches at 90o. As a quaternion, with its four-tuple characteristics that incorporate vector elements, is different from Euler-angle orientation, a new cost function has been developed for the respective MPC controller. In order to achieve singularity-free ori-entations and abate the model infidelity of the system, the quaternion and MPC algorithm have been incorporated for quadrotor flight. Simulation based results elucidate the success of trajectory tracking of quaternion based dynamics of quadrotor using MPC approach.